2020
DOI: 10.1371/journal.pntd.0008610
|View full text |Cite
|
Sign up to set email alerts
|

ISG15 overexpression compensates the defect of Crimean-Congo hemorrhagic fever virus polymerase bearing a protease-inactive ovarian tumor domain

Abstract: Crimean-Congo Hemorrhagic Fever virus (CCHFV; family Nairoviridae) is an extremely pathogenic member of the Bunyavirales order. Previous studies have shown that the N-terminal domain of the CCHFV polymerase (L) contains an ovarian tumor-type protease (OTU) domain with the capability to remove both ubiquitin and ISG15 molecules from proteins. The approximately 200 amino acids-long OTU domain, if ectopically expressed, can interfere with both the induction of antiviral type I interferons (IFN) as well as the IFN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The CCHFV L protein is known to have a number of nontraditional polymerase functions. Although not all of these functions have been characterized, the most studied region is the N-terminal OTU domain and its activity in counteracting the activity of type I interferon (IFN) ( 7 , 9 , 20 ). It is possible that the difference in the activity of CCHFV and AIGV L proteins is due to differences in the ability of these two proteins to modulate the IFN response.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CCHFV L protein is known to have a number of nontraditional polymerase functions. Although not all of these functions have been characterized, the most studied region is the N-terminal OTU domain and its activity in counteracting the activity of type I interferon (IFN) ( 7 , 9 , 20 ). It is possible that the difference in the activity of CCHFV and AIGV L proteins is due to differences in the ability of these two proteins to modulate the IFN response.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, some evidence exists to suggest this may in fact be the case. While not fully elucidated, these functions involve the deconjugation and turnover of ubiquitin and ISG15 ( 8 , 9 ). The OTU domain of AIGV is less sensitive than the CCHFV domain to a modified ubiquitin variant (Ubv-CC4) ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the most fatal virus in humans, CCHFV, is capable of both deubiquitylating and deISGylating target proteins, likely resulting in subversion of both the antiviral and inflammatory responses [126,130]. The inhibition of the CCHFV vOTU resulted in impaired viral replication and infectivity [131,132], suggesting that this deISGylase may be a prime target for further therapeutics to treat CCHFV.…”
Section: Viral Antagonism Of Herc5 and Isgylationmentioning
confidence: 99%
“…Indeed, a reduced activation of key components of the innate immune response (including RIG-I) was observed upon infection with wild-type CCHFV, while infection with a mutated CCHFV whose OTU lacked DUB activity led to the establishment of an antiviral state in infected cells [ 159 ]. However, when associated with the full-length L protein, the ability of the OTU domain to suppress the type I IFN-mediated immune response seems to be reduced [ 155 , 156 , 157 ] and a study using a CCHFV VLP system with a protease-negative OTU mutant in immunocompetent cells revealed that IFN induction was not impacted upon infection [ 166 ], adding more complexity to the understanding of the contribution of the OTU domain in the antiviral response.…”
Section: Escape Of Antiviral Responses By Bunyavirusesmentioning
confidence: 99%